Global research trends in benign paroxysmal positional vertigo: a bibliometric analysis - Hu, Yuanjia; Lu, Yang; Wang, Shengyue; Quan, Xiyu; Ren, Yijia; Rong, Kaiyi; Pan, Sijia; Lu, Xiaoyou; Chen, Lei; Tian, Chenghua; Lei, Jianbo (Frontiers in Neurology, 2023)
Background: Benign paroxysmal positional vertigo is the most common disease with vertigo as the main clinical manifestation and has become a global medical problem affecting a wide range of areas and seriously affecting the quality of human life. Objective: This paper analyzes the current characteristics of BPPV-related research and summarizes the current hot topics and trends with the goal of inspiring the future prevention and treatment of BPPV, thereby improving the differential diagnosis and prevention of peripheral vertigo. Methods: A bibliometric approach was used to collect 1,219 eligible studies on BPPV from four databases - Pubmed, Embase, Scopus and Web of Science - between 1974 and 2022. The characteristics and status of the accumulated scientific output were processed using R and VOSviewer, so that we could visualize any trends or hotspots. Results: The results showed a significant increase in the number of publications, with an average annual growth rate of 21.58%. A possible reason for an especially pronounced peak in 2021 is an increase in the prevalence of BPPV as a result of COVID-19. The new coronavirus became a focus of research in 2021. A total of 3,876 authors published articles in 307 different journals, of which 1,097 were first authors. 15.7% of the articles were published in ACTA OTO-LARYNGOLOGICA, OTOLOGY & NEUROTOLOGY and FRONTIERS IN NEUROLOGY. ACTA OTO-LARYNGOLOGICA is far ahead of other journals in terms of growth rate and the number of articles published. American scholars generated the highest number of articles overall, and the USA had the highest number of international collaborations, followed by Italy and China. The themes of the research centered around three topics, namely the treatment of BPPV, its influencing factors, and diagnosis. Conclusions: There has been a large increase in BPPV-related research over the last 50 years, leading to an increase in related articles and rapid development of the field. Key directions for future research include the improvement of individualized treatment for residual symptoms after initial treatment of BPPV amongst the elderly; effective control of co-morbidities such as osteoporosis; and secondary inner ear disease, such as Meniere's disease.